Трансформація структури Чину Святого Василія Великого в останній третині ХVІІІ ст. - Саламаха, Михайло; Salamakha, Myhajlo (My University, 2015)
У статті розглянуто зміни в структурі Чину Святого Василія Великого в останній третині XVIII ст. Висвітлено процес утворення нових провінцій у складі Чину. Проаналізовано зміни в становищі василіан після поділів Речі Посполитої. Простежено скорочення кількості монастирів та монахів у них, яке спостерігали в зазначений період унаслідок проведення ворожої щодо василіан політики урядами Австрійської та Російської імперій.This article brings forward a study of the structural transformation of the Order of Saint Basil the Great caused by the divisions of the Polish-Lithuanian Commonwealth in the last third of the XVIII century. The author examines all main reasons that forced the Supreme Basilian authorities to divide the Order in a new way at the General Chapter of Torokan (1780) and also history and state of each newly created Province, he reproduces geography of their location in the territory of the states-dividers.
The Structural Transformation of the Order of Saint Basil the Great in the Last Third of the XVIII Century
Keywords: Василіанський чин; василіанський монастир; Австрійська імперія; Російська імперія; Basilian Chin; Kapitula; Basilian monastery; Austrian Empire; Russian Empire